A food web model for the Baffin Bay coastal and shelf ecosystem. Part 1 : Ecopath Technical Report - Pedro, Sara; Kenny, Tiff-Annie; Maps, Frédéric; Lemire, Mélanie; Saint-Béat, Blanche; Babin, Marcel; Tremblay, Jean-Éric; Yunda-Guarin, Gustavo; Moisan, Marie-Ange; Boissinot, Justin; Hoover, Carie; Janjua, Muhammad Yamin; et al. (Elementa: Science of the Anthropocene, 2023)
This work was undertaken as part of a multidisciplinary research project funded by the Marine Observation Prediction and Assessment Network - MEOPAR (at ULaval), Canadian Institute of Health Research – CIHR (at University of Ottawa), and Sentinel North (at ULaval), and hosted at Université Laval, in Canada. The objective of the overall project is to support the food security (i.e., the availability and access to sufficient, safe, nutritious food that meets dietary preference) of Inuit communities of the Eastern Canadian Arctic, as well as to explore ways to adapt to effects of climate change. Inuit fish and hunt local marine species, from invertebrates to fish and marine mammals, which make a large part of their diet and are central to their food security. With temperatures increasing twice as fast as the global average and sea ice becoming thinner and forming later, climate change effects on the distribution and abundance of Arctic marine species are already taking place. To better understand the effects of climate change in important subsistence species, a multi-species model (Ecopath with Ecosim) will be used to inform the development of an integrated ecosystem assessment. The model will be used as a tool to co-create scenarios of ecosystem change with the community of Qikiqtarjuaq, Nunavut, to inform adaptation strategies regarding food security (e.g., potential of new fisheries in the region). This report describes the development of an Ecopath model of the Baffin Bay coastal and shelf ecosystem. The methodology, data used to construct the model, data gaps and limitations are described.